2015
DOI: 10.1177/1744629515605942
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation therapy and anxiety, self-esteem, and emotional regulation among adults with intellectual disabilities

Abstract: This pilot study is a randomized controlled trial on the effects of relaxation on anxiety, self-esteem, and emotional regulation in adults with intellectual disabilities (ID) working in a center of supported employment in France. We studied 30 adults with mild or moderate ID who were split at random into a relaxation group (RG, 15 subjects), who completed 10 sessions of relaxation therapy, and a control group (CG, 15 subjects), who were on a waiting list. The method used is the pretest and posttest. Variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
3
18
0
2
Order By: Relevance
“…Most participants recalled the skills practised in the group (mindfulness and relaxation skills), in line with similar studies (e.g. Bouvet & Coulet, 2015). Participants presented their own pre‐existing coping skills in the group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most participants recalled the skills practised in the group (mindfulness and relaxation skills), in line with similar studies (e.g. Bouvet & Coulet, 2015). Participants presented their own pre‐existing coping skills in the group.…”
Section: Discussionsupporting
confidence: 88%
“…Based on supporters’ narratives, half participants reported a decrease of anxiety and increase of wellbeing which is supported elsewhere (e.g. Bouvet & Coulet, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Psychological changes accompanied with the relaxation experience could be a core component of therapeutic improvement observed as a result of Dohsa-hou treatment, although physical relaxation alone has an important role in improving anxiety ( Fujino, 2016 ). Also, a recent study showed that relaxation intervention improved anxiety and self-esteem in adults with intellectual disabilities ( Bouvet and Coulet, 2016 ). In addition to the Dohsa-hou sessions, group therapy provided opportunities to express feelings and to practice self-directing behavior in interpersonal situations.…”
Section: Discussionmentioning
confidence: 99%
“…Les troubles anxieux et de l'humeur sont souvent comorbides de la DI (APA, 2013;Bouvet & Coulet, 2015). La dépression est régulièrement présente chez les individus présentant une DI.…”
Section: Troubles De L'humeur Et Du Comportementunclassified
“…La participation à un groupe de relaxation durant dix semaines à raison d'une heure à chaque semaine aurait un impact positif sur l'anxiété et la régulation émotionnelle. La technique utilisée consistait en une relaxation progressive des muscles permettant de diminuer les tensions musculaires (Bouvet & Coulet, 2015). Un programme d'entraînement physique de 12 semaines a d'ailleurs permis de réduire significativement l'anxiété comparé au groupe contrôle (Carraro & Gobbi, 2012;.…”
Section: Troubles De L'humeur Et Troubles Anxieuxunclassified